2019
DOI: 10.1371/journal.pcbi.1006199
|View full text |Cite
|
Sign up to set email alerts
|

Learning the sequence of influenza A genome assembly during viral replication using point process models and fluorescence in situ hybridization

Abstract: Within influenza virus infected cells, viral genomic RNA are selectively packed into progeny virions, which predominantly contain a single copy of 8 viral RNA segments. Intersegmental RNA-RNA interactions are thought to mediate selective packaging of each viral ribonucleoprotein complex (vRNP). Clear evidence of a specific interaction network culminating in the full genomic set has yet to be identified. Using multi-color fluorescence in situ hybridization to visualize four vRNP segments within a single cell, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…A striking finding was that for any given intermediate rank, there was not a single specific segment composition of high abundance, but several, more quantitative than qualitatively preferred, partly overlapping segment combinations. This observation indicates a limited variability of specific interactions between the vRNPs, but argues against a strict, non-variable sequence of vRNP interactions consistent with recent experimental and modelling reports 14 , 37 , 38 . In the latter case, we would have expected a single distinct MSC composition to stand out per MSC rank.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A striking finding was that for any given intermediate rank, there was not a single specific segment composition of high abundance, but several, more quantitative than qualitatively preferred, partly overlapping segment combinations. This observation indicates a limited variability of specific interactions between the vRNPs, but argues against a strict, non-variable sequence of vRNP interactions consistent with recent experimental and modelling reports 14 , 37 , 38 . In the latter case, we would have expected a single distinct MSC composition to stand out per MSC rank.…”
Section: Resultssupporting
confidence: 87%
“…argues against a strict, non-variable sequence of vRNP interactions consistent with recent experimental and modelling reports 14,37,38 . In the latter case, we would have expected a single distinct MSC composition to stand out per MSC rank.…”
Section: Resultssupporting
confidence: 81%
“…To further examine a potential packaging defect for the chimeric WSN [pdm-NS 5′] mutant, we performed multi-color fluorescence in situ hybridization (FISH) to assess segment colocalization during viral infection. We focused on the colocalization of the NS with the M segment, as our previous studies have shown that the intracellular distribution of the M segment is highly correlated with the distribution of the NS segment, and that these two segments cluster together in putative vRNA segment assembly network constructions with machine learning [27]. Host cells infected with either wildtype or chimeric mutant virus for both WSN and H1N1pdm backgrounds were fixed and stained with probes at 8 hpi ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…2). This work has led to the concept that IAV packaging is mediated by RNA:RNA interactions, a hypothesis that has been corrob-orated through more current methodologies (Dadonaite et al 2019;Majarian et al 2019). This knowledge of packaging requirements enabled one to build viral recombinants expressing a foreign segment and complement the missing viral protein using stably expressing cell lines (Shinya et al 2004;Martínez-Sobrido et al 2010;Ozawa et al 2011).…”
Section: Defining Iav Circuitrymentioning
confidence: 99%